The Importance of Shear-Dilatancy Behaviors in RC Columns. Issue 3 (September 2013) - Crawford, John E.; Wu, Youcai; Magallanes, Joseph M.; Choi, Hyung-Jin
A recent examination of concrete material models embedded in LS-DYNA revealed that almost all of these models fail to adequately incorporate shear-dilatancy behaviors into their formulations. Shear-dilatancy is particularly important to correctly capturing the resistance exhibited by RC (reinforced concrete) columns that are subjected to lateral loadings, especially if retrofitted with FRP (fiber reinforced plastic). The ramifications of this concern when using LS-DYNA to perform analyses of RC columns retrofitted with FRP are demonstrated in the paper, particularly related to predicting the enhanced lateral resistance afforded by the FRP and the magnitude of lateral deformation associated with its rupture. This paper presents results from tests and high-fidelity physics-based simulations with LS-DYNA to illustrate the importance of capturing shear-dilatancy behaviors when analyzing RC columns, especially ones retrofitted with FRP, where the FRP's tension failure capacity is a major design constraint.